Kinetics of Texture and Colour Changes in Chicken Sausage during Superheated Steam Cooking - Abdulhameed Asmaa A.; Yang Tajul A.; Abdulkarim A. A. (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to develop a kinetic model to describe the texture and colour changes of chicken sausage during superheated steam cooking. Chicken sausages were cooked at temperature ranging from 150-200°C with treatment times ranging from 2-6 mins. The texture profile was evaluated in terms of hardness, cohesiveness, gumminess, and chewiness, while the colour parameters were estimated in terms of lightness (L*), redness (a*), yellowness (b*), and total colour difference (∆E). Experimental data showed a gradual reduction in texture parameters as cooking times and temperatures increased. The L* value of the colour showed a linear reduction with cooking condition, while the a*, b*, and ∆E values showed a contrary effects. The decrease in texture parameters and L*-value of colour parameter followed the first-order kinetic model. While, zero-order kinetic model was adapted to fit the a* and b*. The modified first order kinetic showed a good fit for total ∆E. Significant correlations between colour and texture parameters were observed, which showed that a* alone could be used to predict the texture of chicken sausage.